Development of Articulate Storyline-based Dynamic Fluid Learning Media For Grade XI High School Students - Farah Faridatul Fatikhah; Mita Anggaryani (PendIPA Journal of Science Education, 2022)
Articulate Storyline (AS) is a learning media creation software that presents materials with storylines. The presence of added characters makes the learning media more interactive and more immersed in the story presented. The use of characters is expected to appeal to students learning. The topic used in the learning media developed is Dynamic Fluid. The purpose of this research is to design a physics learning medium that implements Dynamic Fluid theories into a storyline using an Articulate Storyline. According to contextual learning theory, good learning is learning that is applicable to daily life. For further media development, researchers plan to raise the life of a plumber and associate it with Dynamic Fluid materials according to the High School Curriculum. The method used in this study is Research and Development (R&D). Media can be used via web and android. This study stated that the learning media developed is worth using with a validity value of 90.71% classified as very valid. The positive response of students to the media by 99.16%, which belongs to the category, is very good. The percentage of learning activities completed through the comprehension test was 84.4%, which falls into the category of very good. Dynamic fluid learning media based on the Articulate Storyline is suitable for use as a learning resource and as a learning companion for grade 11 high school students.